(untitled) (Revista Apotheke, 2022)
From a self-narrative positioning, this text proposes to launch some ideas on the field os teacher training, taking as a cut the formative stage of the supervised Curricular Internship. For the construction of this thought, the perspectives os atubiography and the notion os nomadic teaching (XXXXXXX) are brought as axes that support a way of conceiving, creating and positioning oneself in the contexto of the visual arts education. Nevertheless, a conversation is established with authors such as Mosé (2018); Rodrigues (2017), among others, that contribute to deepening these reflections.